Exploring Digital Literacy Practices in English Language Learning for Secondary Level Students - Rahman, Arif; Al-Qasri, Selma; Ofara, Wafika (Universitas Pendidikan Mandalika, 2023)
Integrating digital literacy into the teaching and learning process in ELT (English Language Teaching) classes has become a significant challenge for teachers in the 21st century. Digital literacy has evolved beyond being a mere technical skill; it has fundamentally transformed the way learners approach their education. In response to this shift, many English learners, including secondary school students, now rely heavily on advanced utilities and web-based tools to create and share meaning. This paradigm shift has not only influenced the curriculum for English students at SMA IT Abhur Mataram but has also been guided by the global Digital literacy competency framework set forth by UNESCO. The approach taken in this study employs a graphical representation to subjectively depict the advanced levels of English language learning. It identifies seven key areas of higher education skills that play a crucial role in English learning at Abhu Mataram High School. These areas encompass proficiency in equipment and software, mastery of data and information, effective communication and collaboration, content generation using computers, ensuring online security, problem-solving abilities, and career-related skills. In summary, the digital literacy standards established by UNESCO for the broader digital society can be effectively applied within the context of English language learning. These seven areas of computer skills, which are integral to the learning process at Abhur Islamic School Mataram, are systematically integrated into preparatory, intermediate, and concluding exercises, ensuring a comprehensive and up-to-date approach to English education in the digital age.